Basic principles of creation, preparation and application of the system of radio-electronic warfare of the armed forces of the state (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
The article outlines the basic principles, goals and tasks of managing the electronic warfare system of the armed forces at the present stage, as well as the components, forces and facilities of this system and the basic requirements for them.
Keywords: electronic warfare, armed forces, military security, armed conflict, combat use, components, forces and facilities.